2022
DOI: 10.1101/2022.01.17.476220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuron-specific protein network mapping of autism risk genes identifies shared biological mechanisms and disease relevant pathologies

Abstract: Autism spectrum disorder (ASD) is a genetically heterogeneous disorder. Sequencing studies have identified hundreds of risk genes for autism spectrum disorder (ASD), but the signaling networks of genes at the protein level remain largely unexplored, which can provide insight into previously unknown individual and convergent disease pathways in the brain. To address this gap, we used neuron-specific proximity-labeling proteomics (BioID) to identify protein-protein interaction (PPI) networks of 41 ASD-risk genes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 184 publications
1
9
0
Order By: Relevance
“…First, we performed immunoprecipitation coupled with mass spectrometry ( IP- MS ) analysis using an anti-TAOK2β antibody in cytoplasmic lysates from either mouse cortices or N2a cells transfected with wild-type TAOK2β. In parallel, we used a neuronal proximity-based proteomic system to identify protein-protein interaction ( PPI ) networks associated with TAOK2β in mouse cortical neurons (18DIV) infected with lentiviral constructs, expressing a BioID2 fusion protein (pLV-hSyn-tGFP-P2A-TAOK2β-13xLinker- BioID2-3xFLAG) 12 . Co-purified proteins from the three biological samples were involved in chloride channel activity, synaptic structure constituents and translational control based on gene ontology (GO) term analysis (Figure 1 and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we performed immunoprecipitation coupled with mass spectrometry ( IP- MS ) analysis using an anti-TAOK2β antibody in cytoplasmic lysates from either mouse cortices or N2a cells transfected with wild-type TAOK2β. In parallel, we used a neuronal proximity-based proteomic system to identify protein-protein interaction ( PPI ) networks associated with TAOK2β in mouse cortical neurons (18DIV) infected with lentiviral constructs, expressing a BioID2 fusion protein (pLV-hSyn-tGFP-P2A-TAOK2β-13xLinker- BioID2-3xFLAG) 12 . Co-purified proteins from the three biological samples were involved in chloride channel activity, synaptic structure constituents and translational control based on gene ontology (GO) term analysis (Figure 1 and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…pAAV-CAG huTAOK2β wt (plasmid encodes humanTAOK2-short variant) and pAAV-CAG-tDimer2 (plasmid encodes the A tandem dimer mutant of DsRed tagged to the RFP) were used for in utero electroporation of cortical neurons. pLV-hSyn-tGFP-P2A-POI-13xLinker-BioID2-3xFLAG construct expressing BioID2 fusion proteins and Luciferase-P2A-BioID2-3xFLAG construct as a negative control were used in neuron viral infection 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the obtained results, ten genes clearly formed potentially important nodes in the PPI networks. Six of these genes, namely HDAC4, MECP2, TCF4, TRIM33, TTN, and TSC2, belong to the SFARI category 1-2 (highconfidence and strong candidate genes) and are widely associated with the neuropathological mechanisms of ASD [31,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. The CFTR, NOD2, PPP2R2B, and TTR genes were not found in the SFARI databases, and data on the role of 11 Disease Markers these genes in ASD are very sparse [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a considerable genetic heterogeneity underlying ASD, there is compelling evidence that a large number of risk genes can be integrated into a much smaller number of proteinprotein interaction (PPI) networks [26]. Previous studies have shown that ASD genes functionally converge in synapse development, axon alignment, neuron motility, synaptic transmission, chromatin remodeling, transcription and translation regulation, ion transport, and cell adhesion [27][28][29][30][31][32]. As far as we know, these studies were mainly focused on investigating genes affected in children with ASD, but not in relatives with subclinical phenotypes of BAP.…”
Section: Introductionmentioning
confidence: 99%